The transformative potential of artificial intelligence in solid organ transplantation - Al Moussawy, Mouhamad; Lakkis, Zoe S.; Ansari, Zuhayr A.; Cherukuri, Aravind R.; Abou-Daya, Khodor I. (Frontiers in Transplantation, 2024)
Solid organ transplantation confronts numerous challenges ranging from donor organ shortage to post-transplant complications. Here, we provide an overview of the latest attempts to address some of these challenges using artificial intelligence (AI). We delve into the application of machine learning in pretransplant evaluation, predicting transplant rejection, and post-operative patient outcomes. By providing a comprehensive overview of AI's current impact, this review aims to inform clinicians, researchers, and policy-makers about the transformative power of AI in enhancing solid organ transplantation and facilitating personalized medicine in transplant care.